Aprendiendo en movimiento para el desarrollo de la lateralidad en los niños de 4-5 años, de la escuela fisco misional “Fe y Alegría” del cantón Riobamba provincia de Chimborazo período 2015-2016 - Gusniay Padilla, Tamia Natali (2016)
This research called "Learning through Movement for development of laterality in boys and girls of 4-5 years-old at Escuela Fisco Misional Fe y Alegría of Riobamba canton, province of Chimborazo academic term 2015-2016" was performed after that the problem was identified in the institution that was the lack of appropriate techniques to develop laterality in boys and girls, because of this, it was raised a general objective that determines the importance of Learning through Movement for the Development of laterality, articulating with the specific objectives that analyze the level of knowledge of Learning through Movement Strategy for the development of laterality, to identify the degree of development of laterality applying the strategy of Learning through Movement, and investigate various games of Learning through Movement for developing of laterality; in the theoretical framework are the conceptual references in which this study was supported in order to answer the above stated interest. Subsequently, considering the inductive and deductive method, the type of research is descriptive and correlational as well as the documentary and field bibliographic design, and considering the population of 29 boys and girls, with the observation technique and the instrument used it proceeded to the application tab observation in Pre-k 2, the same that has been analyzed and quantified by tables and statistical graphs, enabling reach make appropriate conclusions set out the benefits that the implementation of the program Learning through Movement to promote balance, coordination, tone regarding laterality; finally consist recommendations which encourage the practice of Learning through Movement program which provides a great advantage for the development of motor skills, gross and fine for the seizure of the laterality of boys and girls in Pre-K 2.